The relationship between lumbopelvic flexibility and sitting posture in adult women. (14th February 2019) - Frey, Mona; Poynter, Alison; Younge, Keisha; De Carvalho, Diana
Abstract: Clinical observations have suggested that limited hamstring flexibility may be associated with sagittal spinal curvatures in spine flexed postures. Thus, limited hamstring flexibility may be related to large amounts of spine flexion in "slumped" sitting postures which could contribute to low back pain and injury. The aim of this study was to determine if hamstring and pelvic flexibility are associated with flexed sitting postures using a backless office chair. Forty-one healthy female adults aged 18–69  years were recruited. Subjects performed the Sit-and-Reach test to determine maximum flexibility values and lumbar and pelvic angles were measured with accelerometers. Participants then completed a standardized typing task for a 10-minute sitting trial at an ergonomically adjusted workstation. The results showed no association between hamstring flexibility and seated lumbar spine and pelvic angles (p = 0.999, η 2  = 0.000; p = 0.901, η 2  = 0.006). Greater pelvic flexibility was associated with a more upright lumbar sitting posture (p = 0.023; η 2  = 0.132) but with no specific pelvic sitting posture (p = 0.660; η 2  = 0.005). Different movement strategies during the Sit-and-Reach test were detected: all participants moved through their lumbar spine; but only those with 'excellent' flexibility also used their pelvis. Individuals in the 'excellent' flexibility group were significantly shorter than those with 'poor' and 'good' flexibility (p = 0.020; η 2  = 0.190). In conclusion, hamstring flexibility does not influence sitting posture but pelvic flexibility does. Other factors such as acetabulofemoral joint limitations, consciousness of posture, or the seat itself may also influence sitting posture. Different movement strategies as well as height appear to contribute to the Sit-and-Reach test which should be researched further.